Teaching The Topic of Sulfur and Its Compounds Through Case Technology - M.I.Ibodulloyeva; D.X. Salimova; M.S.Аlimurodov (Genius Journals, 2022)
This article describes situations of students' professional activities and their analysis, the ability to think logically, teamwork skills based on the use of innovative technologies in teaching chemistry to teachers.
Keywords: problematic method; sulphuric acid; sulfur; educational technology